2012
DOI: 10.1007/s12640-012-9339-2
|View full text |Cite
|
Sign up to set email alerts
|

The Rho-Kinase (ROCK) Inhibitor Y-27632 Protects Against Excitotoxicity-Induced Neuronal Death In Vivo and In Vitro

Abstract: Rho-associated coil kinase (ROCK) inhibitors reportedly prevent neurodegeneration, and abnormal ROCK activation in the central nervous system induces neurite collapse and retraction. However, it is unclear whether the ROCK inhibitor Y-27632 directly protects hippocampal neurons from excitotoxicity. Here, we determined the effects of Y-27632 on neuroprotection following kainic acid (KA)-induced seizures in mice and during glutamate-induced excitotoxicity in HT22 cells. One day after Y-27632 injection, mice were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(49 citation statements)
references
References 39 publications
0
48
0
1
Order By: Relevance
“…ROCK is reported to regulate MLC phosphorylation 22. Abnormal activation of ROCK has been observed in the pathophysiology of CNS diseases 55, 56. Our results revealed that ROCK1 was cleaved to form a 30-kDa band upon H 2 O 2 exposure, while ROCK2 was not cleaved.…”
Section: Discussionmentioning
confidence: 55%
“…ROCK is reported to regulate MLC phosphorylation 22. Abnormal activation of ROCK has been observed in the pathophysiology of CNS diseases 55, 56. Our results revealed that ROCK1 was cleaved to form a 30-kDa band upon H 2 O 2 exposure, while ROCK2 was not cleaved.…”
Section: Discussionmentioning
confidence: 55%
“…ROCK-2, the main brain isoform of Rho-kinase [25, 26], has been primarily localised to neurons [25, 27] and non-vascular astrocytes [27, 28] rather than to blood vessels. Because the relevance of ROCK-2 to neurovascular function has not been extensively studied, we first looked at steady state levels of the two ROCK isoform transcripts in human and mouse brain cells which comprise the BBB, namely brain endothelial cells (BECs) and astrocytes, and further compared them to the abundance of ROCK mRNA in neurons.…”
Section: Resultsmentioning
confidence: 99%
“…Two isoforms of ROCK have been described, ROCK-1 (p160ROCK; ROKβ) and ROCK-2 (ROKα) [10, 11]. ROCK-1 is ubiquitously expressed (with low levels in brain and muscle), while ROCK-2 is abundant in the brain [25, 26], particularly in neurons [25, 27] and in reactive astrocytes [27, 28]. The two isoforms share 65% overall amino-acid sequence identity and particularly high homology in the kinase domain (92%) [26, 29].…”
Section: Introductionmentioning
confidence: 99%
“…The blots shown are representative of three independent experiments. effect in various in vitro and in vivo models of neuronal cell death, such as cerebral ischemia and excitotoxicity (29,30). In addition to Rho kinase, Rho GTPase has many other downstream effectors that could contribute to neuronal death via a mechanism that is independent of caspase activation.…”
Section: Volume 290 • Number 15 • April 10 2015mentioning
confidence: 99%